Spectral properties of strawberry plants - M. Deák, Sz.; Márk, G. I.; Szabó, T.; Füleky, Gy. (International Journal of Horticultural Science, 2007)
Strawberry varieties were studied in 3 different growing areas of different soil- and ecological properties in Hungary. We have measured the optical spectra of the leaves together with their nutrient content and performed sensory examinations on the deep frozen and melted fruit. The 6 varieties were Elsanta, Marianna, Spadeka, Symphony, Camarosa, and Raurica. The 3 sites were Újfehértó, Pölöske, and Kecskemet. Colour of the leaves was characterised by their lightness and dominant wavelength. Under non-optimal soil and ecological conditions the varieties could be distinguished by their colour — the leaves became lighter and more yellow. The fruits did not produce the genetically determined taste if the plant can not grow in optimal circumstances — we found a negative correlation between the leaf colour in flowering time and the fruit flavour. Leaf colour measurements performed in flowering time make it possible to improve fruit quality by changing the nutrient supply between flowering and ripening.